2018
DOI: 10.1021/acs.inorgchem.8b00438
|View full text |Cite
|
Sign up to set email alerts
|

Relativity–Induced Bonding Pattern Change in Coinage Metal Dimers M2 (M = Cu, Ag, Au, Rg)

Abstract: The periodic table provides a fundamental protocol for qualitatively classifying and predicting chemical properties based on periodicity. While the periodic law of chemical elements had already been rationalized within the framework of the nonrelativistic description of chemistry with quantum mechanics, this law was later known to be affected significantly by relativity. We here report a systematic theoretical study on the chemical bonding pattern change in the coinage metal dimers (Cu, Ag, Au, Rg) due to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 77 publications
4
10
0
Order By: Relevance
“…By comparing our results with those we find in the literature, we see that this dissociation energy trend is well-known and somehow expected for these complexes. A similar trend is also displayed for group 11 dimers and an analogous trend with the Ag–H showing the lowest value of D e is also reported for group 11 monohydrides …”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…By comparing our results with those we find in the literature, we see that this dissociation energy trend is well-known and somehow expected for these complexes. A similar trend is also displayed for group 11 dimers and an analogous trend with the Ag–H showing the lowest value of D e is also reported for group 11 monohydrides …”
Section: Resultssupporting
confidence: 83%
“…Moreover, the trend found here for dihydrides is very similar to that observed both previously and in the current study for monohydrides (Table S3 in the SI) and also resembles the trend observed for atomic radii , of group 11 metals, which suggests the strong relativistic stabilization of 6s and 7s orbitals to be responsible for the very short Au–H and Rg–H distances, respectively. The same trend has also been observed in a recent work for the M–M distances in group 11 dimers M 2 (M = Cu, Ag, Au, Rg) (Cu < Rg < Au < Ag), where correlated approaches have been used to investigate their spectroscopic constants . The differences between DFT and 4c-CCSD­(T) results point out that a very accurate treatment of electron correlation and relativistic effects is a particularly important ingredient when dealing with these properties …”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…In the case of the coinage metal dimers M 2 from group 11 (Cu 2 , Ag 2 , Au 2 ), the M-M single bond is due to interaction of σ (n−1)d,ns valence-hybrids between the polarized M-(n−1)d 10 closed shell cores. In Rg 2 however, the upper antibonding σ * u−6d 2 orbital has changed its character due to the relativistic 6d 5 / 2 destabilization and 7s½ stabilization to dominantly σ * u,7s 2 type, with remarkable changes of force constant, bond energy and charge and pair density distributions (Li et al, 2018).…”
Section: The Later D-block Elementsmentioning
confidence: 99%
“…The direct and real space observation of relativistic molecular orbitals is exceptional, since most of previous experiments for very few heavy element molecules relied on spectroscopy techniques [28][29][30][31] and, thus, the relativistic effects were mainly discussed in theoretical aspects [32,33]. Although a Pb dimer has a much longer bond length (7 Å) than other relativistic molecules [33][34][35] and there is a substantial adatom-substrate interaction, the molecular splitting mainly arises from the direct overlap of relativistic p orbitals. This is distinguished from the substrate-mediated long-range interaction of other metal clusters on metal surfaces [36,37].…”
Section: Relativistic Molecular Orbitals In Pb Dimersmentioning
confidence: 99%